Knowledge Management Perspective in the Tourism and Hospitality Industry - Anton Florijan Barišić; Joanna Rybacka Barisic\'; Ivan Miloloža (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
The modern business environment is rapidly changing generating unpredictable competitive challenges. Tourism and hospitality industry is specifically vulnerable to such unplanned changes and forced to respond in quick time to address detrimental business situations. It is known for a long time that competitiveness in the global market depends on the organisation's ability to capitalize on its intellectual and knowledge-based assets. In that sense, knowledge is recognized as fairly potent asset supporting organisations and the entire tourism industry in creating an efficient model for achieving competitive advantage and realise their desired business performance. The paper discusses a tourism and hospitality industry model of a knowledge management system including advice and guidance in selecting different concepts and models of knowledge and information flow. Tourism enterprises are quite inefficient in implementing knowledge management concepts and processes due to adverse knowledge adoption environment. Therefore, the paper argues that introduction of the knowledge management practice in tourism sector ensures new opportunities in addressing the challenges of a globalised market and increase the competitiveness and improve the innovative processes in tourism.
Keywords: D83; M10; Z32; D40; 330; Knowledge; Knowledge Management; Tourism and Hospitality Industry; Market